The International Political Consequences of Unification of Germany. Expansion of NATO - Result of Unification of Germany - A. A. Akhtamzjan (Vestnik MGIMO-Universiteta)
The geostrategic consequences of final settlement concerning Germany are investigated in the article, especially the remote consequences of this historical event. Conclusions of the author are based on Russian diplomatic documents as well as the German official documents. Publications of competent experts - germanists (such as V.М. Fаlin, J.A.Kvizinsky, V.P.Terekhov, I.F.Maksimychev) are analyzed in the article. Тhe Author is a well-known researcher of the Russian and German diplomatic archives.